IMPLEMENTASI KIRI ISLAM HASAN HANAFI TERHADAP PENDIDIKAN PESANTREN DI INDONESIA - Wulandari, Agustin; Ahmad Fauzi (Pascasarjana Universitas Al-Qolam Malang, 2025)
This research aims to find out the implementation of the Islamic Left movement in Pesantren education in Indonesia, in order to develop scientific knowledge and to restore the treasures of Islam. This research uses a leatherative method of literature review or literature review with narrative analysis obtained from various sources of books or research journals that are in accordance with the research domain. Pesantren as an example of Islamic education in Indonesia. Pesantren education has a long history, has a culture that prioritizes Islamic values, the education methods applied, and as a medium for da'wah. Pesantren in this modern era is not only focused on cultural education, but also penetrates into science, technology, and economic education. The progress of Pesantren today is in accordance with the vision of leftist Islam Hasan Hanafi who prioritizes scientific renewal which is not only focused on traditional science studies but also examines the science that exists in Indonesia and continues to run formal education provided by the government or the Pesantren itself. Currently, Muslims are experiencing a setback in science and technology where Muslims only enjoy technological products made by Western society. This certainly provides a challenge to Pesantren in this modern era while still prioritizing eastern culture. The need for the implementation of the Islamic Left in education in Pesantren with the presence of education related to IT or science that harmonizes with the Qur'an to develop the curriculum, so that it can enrich the Islamic treasures.